Hubungan Antara Orientasi Nilai (Value Orientation) dengan Paradigma Lingkungan Baru (New Environmental Paradigm) Siswa - Dwi Widyawati, Amalia Fitri (IJEEM - Indonesian Journal of Environmental Education and Management, 2020)
The New Environment Paradigm is the result of interaction of various factors, one of which is the Value Orientation. This research discusses the relationship between the value orientation and the new environmental paradigm for high school students in Jakarta. This research was conducted at SMAN 22 Jakarta in Semester I Academic Year 2019/2020. The method used is a survey method with correlational techniques. The samples used were 100 students of class XI MIPA who were randomly selected. Data is collected using instrument value orientations and new environmental paradigms. Data analysis was performed with a simple linear regression test to measure the relationship used Pearson Product Moment at a significance level of 5%. The results showed a positive and significant relationship between the value orientation with the new environmental paradigm. The sample reliability for the nep variable was 0.857, while the reliability of the comparison of sample values ​​was 0.905. The orientation of the value of the contribution to the new environment paradigm variable was 38.7%. Egoistic has the highest contribution to nepian at breakdown because it involves factors such as the student environment and technology. Therefore value orientation has a role in looking at the paradigm of the new environment of students. Kata Kunci : Value Orientation, New Environmental Paradigm, Students.